Central exclusive diffractive production of the π+π- continuum, scalar, and tensor resonances in pp and pp[bar] scattering within the tensor Pomeron approach - Lebiedowicz, Piotr; Nachtmann, Otto; Szczurek, Antoni (Physical review, 2016)
We consider central exclusive diffractive dipion production in the reactions pp→ppπ+π− and p¯p→p¯pπ+π− at high energies. We include the dipion continuum, the dominant scalar f0(500), f0(980), and tensor f2(1270) resonances decaying into the π+π− pairs. The calculation is based on a tensor Pomeron model and the amplitudes for the processes are formulated in terms of vertices respecting the standard crossing and charge-conjugation relations of quantum field theory. The formulas for the dipion continuum and tensor meson production are given here for the first time. The theoretical results are compared with existing STAR, CDF, CMS experimental data and predictions for planned or current experiments (ALICE, ATLAS) are presented. We show the influence of the experimental cuts on the integrated cross section and on various differential distributions for outgoing particles. Distributions in rapidities and transverse momenta of outgoing protons and pions as well as correlations in azimuthal angle between them are presented. We find that the relative contribution of the resonant f2(1270) and dipion continuum strongly depends on the cut on proton transverse momenta or four-momentum transfer squared t1,2 which may explain some controversial observations made by different ISR experiments in the past. The cuts may play then the role of a ππ resonance filter. We suggest some experimental analyses to fix model parameters related to the Pomeron-Pomeron-f2 coupling.